Comparison of the Heme Iron Utilization Systems of Pathogenic Vibrios - O’Malley, S. M. (American Society for Microbiology, 1999)
Vibrio alginolyticus, Vibrio fluvialis, and Vibrio parahaemolyticus utilized heme and hemoglobin as iron sources and contained chromosomal DNA similar to several Vibrio cholerae heme iron utilization genes. A V. parahaemolyticus gene that performed the function of V. cholerae hutA was isolated. A portion of the tonB1 locus of V. parahaemolyticus was sequenced and found to encode proteins similar in amino acid sequence to V. cholerae HutW, TonB1, and ExbB1. A recombinant plasmid containing the V. cholerae tonB1 and exbB1D1 genes complemented a V. alginolyticus heme utilization mutant. These data suggest that the heme iron utilization systems of the pathogenic vibrios tested, particularly V. parahaemolyticus and V. alginolyticus, are similar at the DNA level, the functional level, and, in the case of V. parahaemolyticus, the amino acid sequence or protein level to that of V. cholerae.